Role of Domestic Banking and Financial Institutions in Project Finance: Insights from Hydropower Sector in Nepal - Nepal, Achyut; Maelah, Ruhanita; Khanal, Vishnu (Journal of Advanced Academic Research, 2023)
Hydropower is a low carbon renewable energy alternative for replacing carbon emission energy sources. In Nepal, this infrastructure sector is being developed for fulfilling the internal demand of electricity. Previous studies emphasized public-private partnership (PPP) utilizing project finance (PF) model in infrastructure sector. Recognizing the importance of domestic banking and financial institutions (BFIs) in project finance this study delves into factors significantly affecting the role of BFIs in project finance. Cross-sectional survey utilizing questionnaires was conducted among respondents representing the independent power producers (IPPs) and BFIs in Nepal. Regression analysis showed predictor variables like economic environment, guidelines of the central bank and low default rate have significant impact on project finance. issues related to adequate legal provision for non-recourse financingrole of BFIs for project finance arrangement. Credibility of hydropower project sponsors is an important determinant in financing hydropower project. The availability of comparatively more bankable projects in other investment sectors against the investible fund constraints resulted in limited complete project finance arrangement of hydropower projects. Detail investigation on guarantees to the lenders against the project loan and improvements needed in legal frameworks to accommodate the non-recourse finance and making economic and legal environment friendlier to private sector is the limitation of this study left for future researches.